Screening of natural colours from various natural resources as potential reusable visual indicators for monitoring food freshness - Abdul Rahim, Mohd. Zulkhairi; Husin, Nurdiyana; Mohd Noor, Mohd. Azizan; Yet, Zaida Rahayu; Ismail-Fitry, Mohammad Rashedi (Malaysian Society of Analytical Sciences, 2020)
Natural colours have emerged as an alternative source of colours due to the high demand and public sensitivity towards the risk of using synthetic colours. Natural colours are non-hazardous and made from renewable resources, in which the supply is abundant and not harmful to the environment. This study aims to screen naturally-derived colours from butterfly pea, red cabbage, turmeric, and beetroot as visual indicators in monitoring food freshness. The study was carried out in three stages: the extraction of natural colours, the absorption of natural colours on the indicator paper, and the application of visual indicators on the real sample. The results showed that all visual indicators changed their colours towards the spoilage of meat in 24-h monitoring at room temperature. The most significant colour change was observed on the natural colour from butterfly pea compared to other natural resources. HS-SPME-GC-FID analysis confirmed the presence of methylamine as the main volatile compound from the spoiled meat, which contributed to the colour change of the visual indicators. FTIR analysis of useable indicators indicated the presence of amine compound (N-H) that aligned with the result of HS-SPME-GC-FID. The used visual indicators returned to their initial colours and characteristics, which provide the possibility for the fabrication of reusable visual indicators in the future.